Web-Based Patient Queue Number Registration Application at the Sidodadi Community Health Center in Sidoarjo Regency - Muhammad Nabila Akmal Wijaya; Suci Ariani (CV. Media Digital Publikasi Indonesia, 2025)
The main role of Information Technology in today's society is very dominant, and its development is happening rapidly. This technology allows us to quickly and accurately access and process information. In this case, the Sidodadi Community Health Center, located in Sidoarjo Regency, has made efforts to improve the efficiency of outpatient registration. Currently, the patient registration system is still manual, which results in long service times. This study aims to present an innovation by developing a web-based registration system. This application simplifies and optimizes the queuing process, both for users who want to take a queue number and for administrators who call queue numbers. The use of web-based technology is the right solution to improve service quality. This study has limitations in that the application development is only focused on the Sidodadi Community Health Center, Sidoarjo Regency. The main objective of this study is to produce an efficient web-based patient queue number registration application. This application will improve the patient experience, facilitate more structured queue management for Community Health Center staff, reduce patient waiting times, and provide accessibility for patients to monitor their queue information online. The method used in this study is the waterfall method, which has five stages, namely communication, planning, modeling, construction, and deployment. The application development methodology involves needs analysis, system design using the programming languages used in this study, namely PHP, HTML, CSS, and JavaScript, web-based application development, testing, and evaluation. The test results showed that the system successfully provided queue numbers in accordance with the correct queue order, and the user interface was easy to use. This study concluded that the development of the Sidodadi Community Health Center Web-Based Patient Queue Information System successfully improved the efficiency of patient registration and improved the quality of services at the Community Health Center.